3D-printing methacrylate/chitin nanowhiskers composites via stereolithography: Mechanical and thermal properties. (2020) - Maalihan, Reymark D.; Pajarito, Bryan B.; Advincula, Rigoberto C.
Abstract: We report on the mechanical and thermal properties of stereolithography (SLA) 3D-printed methacrylate (MA) resin reinforced by chitin nanowhiskers (CNWs). CNWs were synthesized by acid hydrolysis of crab shell chitin and nanocomposites with 0 wt%, 0.5 wt%, 1.0 wt%, and 1.5 wt% CNWs loading were prepared by slurry compounding method. The obtained CNWs (diameter = 23 ± 5 nm, length = 253 ± 100 nm, and aspect ratio = 11 ± 3) are well dispersed within the bulk of MA at 1.0 wt% loading, implying good interfacial adhesion between the nanofiller and the resin matrix possibly due to hydrogen bonding interactions. The addition of up to 1.0 wt% CNWs to neat MA enhances the tensile strength, strain at break, modulus, and maximum thermal degradation temperatures of the nanocomposites. Moreover, the incorporation of CNWs not only improves the mechanical and thermal properties, but also preserves the excellent resolution and accuracy of 3D-printed MA/CNWs nanocomposites.